Predictors of adverse outcomes after transcatheter mitral valve replacement. (3rd August 2019) - Overtchouk, Pavel; Piazza, Nicolo; Granada, Juan F.; Modine, Thomas
ABSTRACT: Introduction : Transcatheter mitral valve replacement (TMVR) is still a recent technology with numerous unknowns but also great promises. The risk of complications reported in observational studies have limited its adoption by interventional cardiology and surgical communities. Areas covered : Some of the major setbacks of TMVR are complications related to the devices and those related to the pathway. Device-related complications include left ventricle outflow tract (LVOT) obstruction, transcatheter heart valve (THV) dislocation or embolization, thrombosis, and stroke. The transapical approach currently remains the main pathway for TMVR but is associated with high risk of major bleeding and residual apical myocardial scarring. Complication prediction and prevention seem possible. Device-related complication prediction is based on pre-operative imaging including multi-slice computed tomography with 3-dimensional reconstructions and echocardiography which allow LVOT obstruction prediction and appropriate sizing aiming at avoiding dislocation. Industry should aim at the development of transfemoral delivery systems. Nevertheless, several recent feasibility observational studies suggested acceptable safety and efficacy of transcatheter mitral valve replacement. Expert opinion : TMVR complications and transapical delivery are some of the main setbacks which need to be addressed for TMVR to be adopted for broad clinical use.